The Head Room Experience in Implementing the Nursing Management Function during the Covid-19 Pandemic in General Hospital Sabang: A Phenomenology Study - Zuliani, Amanda; Tharida, Maimun; Putra, Yadi; Riza, Saiful; Pratama, Urip (Universitas STRADA Indonesia, 2022)
Background: Nursing is one of the important services for hospital to maintain the quality of services that ensure patient safety. Good nursing services can be seen from the nursing management function carried out by the head of the room, especially in the inpatient room. Purpose: This study explored in depth the experience of the head of the inpatient ward in implementing the nursing management function during the COVID-19 pandemic. Methods: This study used qualitative design with a phenomenological approach. There were six participants in this study. The data collection method used in-depth interviews with guidelines. Data collection used the interview guidelines and field notes in this study. Results: The results of this study consisted of five themes, namely planning not according to needs, organizing according to conditions, staffing improvements, optimized the directing and follow-up the controlling. Conclusion: Hospital need to provide training to ward heads and nurses as well as make improvements to evaluate and develop strategies for hospital during a pandemic based on the obstacles the ward head encountered while managing inpatient room.